Salicylic acid signaling integrates immunity and metabolic regulation to govern nonhost resistance in potato against Phytophthora capsici - Beini Zhang; Huijie Wang; Yanan Huang; Yanhong Fu; Yexin Wu; Juan Du; Hongyang Wang (Plant Science, 2026)

Ultrahigh-resolution flexible quantum-dot light-emitting diodes via dual assembly and transfer printing - Xin Hu; Yangbin Zhu; Runzhen Sun; Zhen Wang; Jiayu Sun; Qinghong Lin; Yi Jiang; Hongyang Fu; Kejia You; Xuan Guo; Yue Wang; Deli Li; et al. (Chemical Engineering Journal, 2026)

Nanomaterials as plant delivery carriers: transport mechanisms and design principles - Ye Li; Yezhuo Zhang; Zhun Zhang; Xi Zhang; Hongyang Wu; Man Zhang; Zhuo Li; Yinglang Wan; Yujie Fu; Wei Dong; Ruili Li; Jinxing Lin (Science China Life Sciences, 2026)

Discovery of isotope 153Hf near the proton drip line via isochronous mass spectrometry: extending the nuclear landscape with HIAF - Hongfu Li; Min Zhang; Hongyang Jiao; Xing Xu; Chaoyi Fu; Jinyang Shi; Jiahao Lv; Xu Zhou; Yuanming Xing; Mingze Sun; Yuhu Zhang; Xiaohong Zhou; et al. (Science Bulletin, 2026)

Load mitigation in floating wind turbines via active tuned mass damper using a physics-informed neural network based controller - Jianing Fu; Shuyue Lin; Hongyang Dong; Xiaowei Zhao (Ocean Engineering, 2026)

Corrigendum to “Preparation of a chitosan/polyvinyl alcohol-based dual-network hydrogel for use as a potential wound-healing material for the sustainable release of drugs” [Carbohydrate Polymers, Volume 348, Part A, 2025, 122822] - Hongyang Guo; Haiying Luo; Juanying Ou; Jie Zheng; Caihuan Huang; Fu Liu; Shiyi Ou (Carbohydrate Polymers, 2026)

Warming‐Induced Carbon Vulnerability in Permafrost Forests: A Shift in Q 10 From Continuous to Discontinuous Zones - Changjiang Huang; Tadeo Sáez‐Sandino; Guiyao Zhou; Lingyan Zhou; Tongyao Kong; Yuling Fu; Hongyang Chen; Yimin Zhu; Shuying Qiu; Kui Xue; Chongwei Fan; Lei Cao; et al. (Global Change Biology, 2026)
Permafrost forests harbor vast, climate‐sensitive carbon (C) reservoirs whose vulnerability largely depends on temperature sensitivity of microbial respiration ( Q 10 ). However, substantial uncertainties persist in predicting Q 10 patterns due to complex interactions among multiple ecological factors. Here, we conducted a standardized field survey with controlled incubations across a regional gradient from continuous permafrost (CP) and discontinuous permafrost (Dis‐CP, including sporadic and isolated ones) in the Greater Khingan Mountains to quantify Q 10 values and identify their main ecological controls. We found that the Q 10 values were significantly higher in CP than Dis‐CP forests, indicating a stronger microbial respiratory response to warming in the coldest permafrost regions. Statistical analysis revealed that the soil microbiome was the most important factor explaining Q 10 values in CP forest (47.8%), whereas a distinct set of factors (plant production, fine texture, substrate quality, and mean annual ground temperature) explained the largest proportion (63.2%) of Q 10 variation in Dis‐CP forests. Our findings suggest that warming‐induced permafrost degradation is likely to shift the dominant controls for Q 10 from microbial community to abiotic and plant‐related factors, while enhancing greenhouse gas emissions from permafrost soils.

Raman mapping reveals alpha radiation damage zonation and its annealing in Durango apatite - Xiaowei Zeng; Guido Pastore; Chuanbo Shen; Alberto Resentini; Hongyang Fu; Chaoqun Yang; Yannick Buret; Pieter Vermeesch; Marco G. Malusà (Earth and Planetary Science Letters, 2025)

Characterization of key aroma compounds in Maillard reaction products of Agrocybe aegerita enzymatic hydrolysates by GC×GC-O-MS - Hongyang Meng; Fan Yang; Shaobo Zhen; Anzhen Fu; Shuang Bi; Ye Liu (Food Bioscience, 2025)

High loading of anthocyanin on chitosan films by acrolein for sensitive monitoring of meat freshness - Hongyang Guo; Haiying Luo; Caihuan Huang; Jie Zheng; Fu Liu; Juanying Ou; Shiyi Ou (Food Chemistry, 2025)

Nitrogen input alleviates the priming effects of biochar addition on soil organic carbon decomposition - Xuhui Zhou; Zhiqiang Feng; Yixian Yao; Ruiqiang Liu; Junjiong Shao; Shuxian Jia; Yining Gao; Kui Xue; Hongyang Chen; Yuling Fu; Yanghui He (Soil Biology and Biochemistry, 2025)

A large-scale FireLine global positioning method based on a single unmanned aerial vehicle - Yifan Fu; Haiyu Zhang; Xingdong Li; Chuanying Lin; Yue Ma; Hongyang Zhao; Shufa Sun (International Journal of Remote Sensing, 2025)

Preparation of a chitosan/polyvinyl alcohol-based dual-network hydrogel for use as a potential wound-healing material for the sustainable release of drugs - Hongyang Guo; Haiying Luo; Juanying Ou; Jie Zheng; Caihuan Huang; Fu Liu; Shiyi Ou (Carbohydrate Polymers, 2025)

ETGC2-net: an enhanced transformer and graph convolution combined network for landslide detection - Shuaishuai Fan; Yibin Fu; Weiming Li; Hongyang Bai; Yonghua Jiang (Natural Hazards, 2025)

EchoSegDiff: a diffusion-based model for left ventricular segmentation in echocardiography - Huijuan Tian; Lei Zhang; Xuetong Fu; Hongyang Zhang; Yuanquan Wang; Shoujun Zhou; Jin Wei (Medical & Biological Engineering & Computing, 2024)

N6-methyladenosine demethylase FTO regulates neuronal oxidative stress via YTHDC1-ATF3 axis in arsenic-induced cognitive dysfunction - Lixiao Zhou; Renjie Li; Fu Wang; Ruiqi Zhou; Yinyin Xia; Xuejun Jiang; Shuqun Cheng; Fanghong Wang; Danyang Li; Jun Zhang; Lejiao Mao; Xuemei Cai; et al. (Journal of Hazardous Materials, 2024)

Opposite effects of soil pH on bacteria and fungi β diversity in forests at a continental scale - Changjiang Huang; Yanghui He; Lingyan Zhou; Ruiqiang Liu; Hongyang Chen; Zhenggang Du; Yuling Fu; Yimin Zhu; Yuxuan Zhou; Chuansheng Wu; Guiyao Zhou; Xuhui Zhou (Journal of Environmental Management, 2024)

A transition from arbuscular to ectomycorrhizal forests halts soil carbon sequestration during subtropical forest rewilding - Ruiqiang Liu; Xuhui Zhou; Yanghui He; Zhenggang Du; Hongyang Chen; Yuling Fu; Liqi Guo; Guiyao Zhou; Lingyan Zhou; Jie Li; Hua Chai; Changjiang Huang; et al. (Science of The Total Environment, 2024)

Manganese/iron organic frame material derivatives for rapid catalytic oxidation of metronidazole: Performance and mechanism - Hongyang Jiang; Zhiyong Zhang; Mingze Fang; Jiuming Hu; Ming-Lai Fu; Lei Chen; Baoling Yuan (Journal of Water Process Engineering, 2024)

Integrating untargeted and pseudotargeted metabolomics and network analysis reveals the interventional effects of red yeast rice on rat serum metabolites - Ge Xun; Yingxuan Li; Yifan Zhang; Song Li; Yanhua Gao; Yujuan Chen; Ding Zhang; Hongyang Ni; Fangfang Liu; Yan Fu; Xu Wang; Qiao Wang (Food Bioscience, 2024)

Mycorrhizal associations relate to stable convergence in plant–microbial competition for nitrogen absorption under high nitrogen conditions - Zhenggang Du; Lingyan Zhou; Madhav P. Thakur; Guiyao Zhou; Yuling Fu; Nan Li; Ruiqiang Liu; Yanghui He; Hongyang Chen; Jie Li; Huimin Zhou; Ming Li; et al. (Global Change Biology, 2024)
Nitrogen (N) immobilization (Nim, including microbial N assimilation) and plant N uptake (PNU) are the two most important pathways of N retention in soils. The ratio of Nim to PNU (hereafter Nim:PNU ratio) generally reflects the degree of N limitation for plant growth in terrestrial ecosystems. However, the key factors driving the pattern of Nim:PNU ratio across global ecosystems remain unclear. Here, using a global data set of 1018 observations from 184 studies, we examined the relative importance of mycorrhizal associations, climate, plant, and soil properties on the Nim:PNU ratio across terrestrial ecosystems. Our results show that mycorrhizal fungi type (arbuscular mycorrhizal (AM) or ectomycorrhizal (EM) fungi) in combination with soil inorganic N mainly explain the global variation in the Nim:PNU ratio in terrestrial ecosystems. In AM fungi‐associated ecosystems, the relationship between Nim and PNU displays a weaker negative correlation ( r = −.06, p r = .25, p

Integration of bimetallic CuCo into N-doping SiC hollow nanoreactor for pollutant removal coupled solar-driven cleanwater regeneration - Rongrong Du; Hongyang Zhu; Shuo Wang; Hongyao Zhao; Mengting Liu; Yanyun Wang; Yiyan Song; Fu Yang (Journal of Environmental Chemical Engineering, 2024)

Preparation of acrolein/resveratrol-grafted chitosan-sodium alginate bilayer films and their antibacterial and antioxidant activities - Hongyang Guo; Kaiyu Jiang; Juanying Ou; Caihuan Huang; Fu Liu; Jie Zheng; Shiyi Ou (Food Hydrocolloids, 2024)

Microplastics as potential barriers to ultraviolet light emitting diode inactivation of MS2 bacteriophage: Influence of water-quality parameters - Jiuming Hu; Zhiyong Zhang; Xiaoxue Li; Xiaochao Bi; Hongyang Jiang; Wenjie Sun; Ming-Lai Fu; Baoling Yuan (Science of The Total Environment, 2024)

Co-application of biochar and organic amendments on soil greenhouse gas emissions: A meta-analysis - Jia Fu; Xuhui Zhou; Yanghui He; Ruiqiang Liu; Yixian Yao; Guiyao Zhou; Hongyang Chen; Lingyan Zhou; Yuling Fu; Shahla Hosseini Bai (Science of The Total Environment, 2023)

Potential use of gluten hydrolysate as a plasticizer in high-moisture soy protein–gluten extrudates - Zhaojun Wang; Yan Ji; Liwei Fu; Hongyang Pan; Zhiyong He; Maomao Zeng; Fang Qin; Jie Chen (Journal of Food Engineering, 2023)

Constructing functional thermal-insulation-layer on Co3O4 nanosphere for reinforced local-microenvironment photothermal PMS activation in pollutant degradation - Mengting Liu; Hongyang Zhu; Rongrong Du; Wuxiang Zhang; Weilong Shi; Zengjing Guo; Sheng Tang; Edison Huixiang Ang; Jun Yang; Jianming Pan; Fu Yang (Journal of Environmental Chemical Engineering, 2023)

Zircon-based proxies for source-rock prediction in provenance analysis: A case study using Upper Devonian sandstones, northern South China Block - Guanzhong Shi; Bastian Wauschkuhn; Lothar Ratschbacher; Chuanbo Shen; Hongyang Fu; Sonja Frölich (Sedimentary Geology, 2023)

Modulating photothermal properties by integration of fined Fe–Co in confined carbon layer of SiO2 nanosphere for pollutant degradation and solar water evaporation - Rongrong Du; Hongyang Zhu; Hongyao Zhao; Hao Lu; Chang Dong; Mengting Liu; Fu Yang; Jun Yang; Jun Wang; Jianming Pan (Environmental Research, 2023)

AIFM1 variants associated with auditory neuropathy spectrum disorder cause apoptosis due to impaired apoptosis-inducing factor dimerization - Yue Qiu; Hongyang Wang; Huaye Pan; Jing Guan; Lei Yan; Mingjie Fan; Hui Zhou; Xuanhao Zhou; Kaiwen Wu; Zexiao Jia; Qianqian Zhuang; Zhaoying Lei; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Soil microbial communities and their co-occurrence networks in response to long-term Pb–Zn contaminated soil in southern China - Hongyang Xu; Bingqing Fu; Jiaqi Lei; Hui Kang; Jun Wang; Xinhao Huang; Fan Zhu (Environmental Science and Pollution Research, 2022)

Deficiency of Klc2 Induces Low-Frequency Sensorineural Hearing Loss in C57BL/6 J Mice and Human - Xiaolong Fu; Yachun An; Hongyang Wang; Peipei Li; Jing Lin; Jia Yuan; Rongyu Yue; Yecheng Jin; Jiangang Gao; Renjie Chai (Molecular Neurobiology, 2021)

Post-Orogenic Tectonic Evolution of the Jiangnan-Xuefeng Orogenic Belt: Insights from Multiple Geochronometric Dating of the Mufushan Massif, South China - Chuanbo Shen; Di Hu; Kyoungwon Min; Chaoqun Yang; Xiaowei Zeng; Hongyang Fu; Xiang Ge (Journal of Earth Science, 2020)

Microbiota transplantation reveals beneficial impact of berberine on hepatotoxicity by improving gut homeostasis - Chenjie Qin; Huilu Zhang; Linghao Zhao; Min Zeng; Weijian Huang; Gongbo Fu; Weiping Zhou; Hongyang Wang; Hexin Yan (Science China Life Sciences, 2018)